Peningkatan Aktivitas dan Prestasi Belajar Bahasa Arab melalui Media Digital Wordwall di Madrasah Aliyah - Rahel Mariyam; Azida Noor Batubara; Nisrina Qurrotu A; Suci Wulandari; Ummi Atiyah; Sopiatun Nawa (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to improve students’ learning activities and academic achievement in Arabic language learning through the use of Wordwall as a digital learning medium in Madrasah Aliyah. The research employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were students of Madrasah Aliyah. Data were collected through observations of students’ learning activities, achievement tests, student response questionnaires, and learning documentation. The collected data were analyzed using descriptive quantitative and qualitative techniques to systematically describe changes in students’ learning activities and learning outcomes. The findings reveal a significant improvement in both learning activities and academic achievement across each cycle. Students’ learning activities increased from 42% in the pre-cycle to 67% in Cycle I and reached 87% in Cycle II. In addition, students’ average achievement scores improved from 61 in the pre-cycle to 74 in Cycle I and further increased to 88 in Cycle II. Classical learning mastery also showed a substantial improvement, rising from 28% to 91%. These results indicate that Wordwall is effective as a digital learning medium for enhancing student engagement and academic achievement in Arabic language learning at the Madrasah Aliyah level.